Participatory on-farm evaluation of new orange-fleshed sweetpotato varieties in Southern Ethiopia - Aragaw, A.; Biazin, B.; Gurmu, F.; Anthony, R.; Cherinet, M.; Low, Jan W.; Yeshitela, M.; Girma, A.; Feyissa, T. (Walter de Gruyter GmbH, 2024)
Sweetpotato is the second most important root crop in Ethiopia, making an important contribution to food security in the densely populated areas of southern Ethiopia. While the white-fleshed sweetpotato (WFSP) varieties have been widely grown, the recently bred pro-vitamin A orange-fleshed sweetpotato (OFSP) varieties are also gaining popularity nationwide. This study evaluated on-farm performances of five new OFSP varieties along with two previously released “check” varieties, one of which is a WFSP, across 13 locations in southern Ethiopia for 2 consecutive seasons (2017 and 2018) with the objective of selecting farmer preferred varieties. The experimental design used was randomized complete block design. Results revealed highly significant differences (p < 0.05) among the tested varieties for all parameters considered. Overall, the new varieties were superior to the check varieties for most of the parameters considered. Kulfo, the OFSP check and the only OFSP variety under production, was inferior in above-ground biomass yield, taste, vegetative, and physical root quality performance. There was a strong negative correlation between altitude and root yields, with the highest root yields being in areas 1,500–1,650 m above sea level. The new varieties were accepted by the farmers due to their better yields, adaptability to the local agro-ecological conditions, and high dry matter content. The results of this study implied that the conventional variety evaluations should be complemented by farmers' participatory processes to ensure the release of acceptable varieties targeting both food security and marketability.